Meningkatkan Hasil Belajar Siswa melalui Pengembangan Perangkat Pembelajaran Berbasis Quantum Learning Pada Materi Hidrokarbon dan Minyak Bumi - Muhammad Fakhrurrazi; Mohammad Masykuri; Sarwanto Sarwanto (Postgraduate, University of Mataram, 2022)
The study aims to develop a quantum learning-based learning instrument on hydrocarbon and petroleum; determine the feasibility of quantum learning-based learning instrument on hydrocarbon and petroleum, and determine the effectiveness of quantum learning-based learning instrument on hydrocarbon and petroleum to improve student's learning outcomes. This type of research is research and development (R&D) using the ADDIE model (analysis, design, development, implementation, and evaluation). The product developed consists of a syllabus, lesson plans, teaching materials, and assessment instruments. The validation results were analyzed using Aiken's validation obtained a validity coefficient of more than 0.80 or categorized as valid and suitable for use. The effectiveness test results were analyzed using SPSS22 obtained t-count > t-table, so it could conclude that quantum learning-based learning tools on hydrocarbon and petroleum materials were effective for improving student learning outcomes.